Efek Hepatoprotektif Ekstrak Etanol Bit Merah (Beta vulgaris L.) terhadap Kerusakan Sel Hepar Mencit (Mus musculus) yang Dipapar Minyak Kelapa Sawit Pemanasan Berulang - Muthmainah, .; Widyaningsih, Vitri (Nexus Biomedika, 2014)
Background: Red beet (Beta vulgaris L.) contains betalain pigments consisting of betacyanin and betaxanthine that can protect the liver from free radicals. This research aims to know the hepatoprotective effect of ethanol extract of red beet against liver histological damage of mice caused by reheated palm oil. Methods: This study was laboratory experimental research with the post test only control group design. This research used male Swiss Webster mice with 2-3 months old and ±20 g of body weight, each. Thirty samples of mice were divided into 5 groups, each group consisted of 6 mice. Sampling technique in this research was consecutive sampling. The normal control group (KKn) was given distilled water. The exposure group (KP) and the 1st, 2nd, 3rd treatment group (KP1, KP2, KP3), mice were given reheated palm oil. KP1, KP2, KP3 were not only given reheated palm oil, but also were given ethanol extract of red beet in dose 5.6 mg, 11.2 mg, and 22.4 mg. These treatments were done for 14 days. On the 15th day mice were killed with neck dislocation and livers were made for preparation with Paraffin Block method and were stained with Hematoxyllin Eosin (HE). Liver histological features were assessed based on quantifying of necrotic cells (pyknosis, karyorrhexis, karyolysis) of each 100 cells in the third zone. Data were analyzed using One-Way ANOVA test and Post Hoc test. Results: Data showed mean of necrotic cells in KKn, KP, KP1, KP2, KP3 respectively were 27.17±1.47, 75.33±1.61, 61.92±1.56, 51±1.54, 43.08±1.73 and mean difference between KP-KP1, KP1-KP2, KP2-KP3 were 13.42, 10.92, 7.92. The results of One-Way ANOVA test showed a significant difference of liver damage score in the five groups, p < 0.001. The results of Post Hoc test also showed significant difference among five groups, p < 0.001 and the most significant difference were between KP-KP2. Conclusion: Ethanol extract of red beet provides protective effect against mices liver histological damage caused by reheated palm oil and optimal dose of ethanol extract of red beet is 11.2 mg/20 g of body weight. Keywords: Ethanol extract of red beet, reheated palm oil, liver histological damage.